MOTIVATIONAL STRUCTURE OF YOUNG CHEMISTS - High, Radka (Journal of Education Culture and Society, 2019)
Aim: the goal of this study is to investigate the motivational structure of participants of Chemistry Olympiad summer camps. The participants are young students who achieved  the best results in chemistry olympiads. Chemistry is one of the least popular subjects among czech students and therefore is important to understand what motivates extraordinary, or gifted students, to learn.Methods: participants (N=38) completed a combination of qualitative and/or quantitative questionnaires. The primary questionnaire, known as the Motivational Induction Method (MIM), is a quality-quantitative questionnaire that uses the principle of open-ended questions. This method can provided a deep understanding of participants´ plans, desires and wishes but also fears, inhibitions or problems. Other questionnaires used were: the Learning Motivation questionnaire and the Achievement Motivation questionnaire which measure the sources of motivation and proportion of achievement needs, respectively.Result: the MIM questionnaire, providing qualitative-quantitative analysis, showed that participants´motivation was mainly focused on self (identity) and contact with others (social motivation). The Learning Motivation questionnaires revealed that the two most important motivational sources for learning chemistry were: one, the acquisition of a good profession in the future (instrumental motivation); and two, cognitive movitavation, or simply the positive feeling one experiences from learning something new.  The Achievement Motivational questionnaires revealed that participants´ need to avoid failure was lower in comparison to general pupils.